Radical Softness as a Tool to Dismantle and Rebuild our Human-AI Future - Eklund, Lina (Imaginations, 2026)
This article presents P, a speculative chatbot experienced as an interactive installation that explores how radical softness can reframe human–AI relations. Challenging techno-utopian narratives of AI as objective, efficient, and solution-oriented, P foregrounds AI’s situated weaknesses, including bias, error, partiality, and environmental cost. Encountered through a physical booth and a soft, heart-shaped controller, users engage an AI that openly acknowledges its dependence on human-made data. Drawing on auto-ethnographic and reflective design methods, the article argues that radical softness can function as a critical design strategy, provoking alternative imaginaries in which AI reflects shared vulnerability rather than technological perfection.